Array languages and the N‐body problem. (5th July 2013) - Cockshott, P.; Gdura, Y.; Keir, P.; Qiu, Judy; Foster, Ian; Taylor, Ronald; Loidl, Hans‐Wolfgang; Singer, Jeremy
SUMMARY This paper is a description of the contributions to the Scottish Informatics and Computer Science Alliance Multi‐core Challenge on many body planetary simulation made by a compiler group at the University of Glasgow. Our group is part of the Computer Vision and Graphics research group, and we have for some years been developing array compilers because we think these are a good tool both for expressing graphics algorithms and for exploiting the parallelism that computer vision applications require. We shall describe experiments using two languages on two different platforms, and we shall compare the performance of these with reference C implementations running on the same platforms. Finally, we shall draw conclusions both about the viability of the array language approach as compared with other approaches used in the challenge and also about the strengths and weaknesses of the two, very different, processor architectures we used. Copyright © 2013 John Wiley & Sons, Ltd.